The Role of PPKN Teachers' Pedagogic Competence in The Moral Development of Junior high school Students in Medan Indonesia - Pardede, Lukman; Silaban, Bajongga; Pardede, Dewi Lestari; Naibaho, Tutiarny; Rince, Rince (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
This study aims to determine how the role of pedagogic competence of Civics teachers in fostering student morale at UPT SMP Negeri 37 Medan. The research method used by the author is a simple quantitative descriptive. The population in this study was 192 students at UPT SMP Negeri 37 Medan from class VIII-A to VIII-F. So the sample in this study was 15% of the total population so that the authors obtained a sample of 29 students using a random sampling technique. Data collection techniques in this study were direct observation to the UPT SMP Negeri 37 Medan, distributing questionnaires, interviews, and documentation. The data that has been collected was analyzed through a simple calculation technique using a frequency table. The results obtained in this study is that the role of pedagogic competence of PPKn teachers has not played a maximum role in carrying out student moral development at UPT SMP Negeri 37 Medan. From the results of the calculation of this research table shows that 56.54% which means this percentage is categorized as quite good/medium. So that the role of the pedagogic competence of PPKn teachers still needs to be further improved, such as the mastery and application of learning tools and media that must involve students being active in the classroom, then the first step taken in conducting student moral development is to look at gender, ethnicity and religion, then by So the moral development of students can run as expected.Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana peranan kompetensi pedagogik guru PPKn dalam pembinaan moral siswa di UPT SMP Negeri 37 Medan. Adapun metode penelitian yang digunakan penulis ialah deskriftif kuantitatif sederhana. Jumlah populasi dalam penelitian ini sebanyak 192 orang siswa di UPT SMP Negeri 37 Medan dari kelas VIII-A sampai dengan VIII-F. Maka yang menjadi sampel dalam penelitian ini adalah 15% dari jumlah populasi sehingga penulis memperoleh sampel sebanyak 29 siswa dengan menggunakan teknik sampel acak. Teknik pengumpulan data dalam penelitian ini adalah observasi secara langsung ke UPT SMP Negeri 37 Medan, menyebarkan angket, wawancara, dan dokumentasi. Data yang telah terkumpul dianalisis melalui teknik perhitungan sederhana dengan menggunakan tabel frekuensi. Hasil yang diperoleh dalam penelitian ini ialah Peranan kompetensi pedagogik guru PPKn belum berperan secara maksimal dalam melakukan pembinaan moral siswa di UPT SMP Negeri 37 Medan. Dari hasil perhitungan tabel penelitian ini menunjukkan bahwa 56,54% yang berarti persentasi ini dikategorikan cukup baik/sedang. Sehingga peranan kompetensi pedagogik guru PPKn masih perlu ditingkatan lagi, seperti penguasaan dan penerapan perangkat dan media pembelajaran yang harus melibatkan siswa bersikap aktif dikelas, kemudian adapun langkah pertama yang dilakukan dalam melakukan pembinaan moral siswa ialah melihat dari jenis kelamin, suku dan agama, maka dengan begitu pembinaan moral siswa dapat berjalan sesuai yang diharapkan.